#TITLE_ALTERNATIVE# - FARUQI (nim : 13314002) - M. BRAHMA WALUYA (nim : 13314041), ISMAIL
An increase in the human population leads directly to the need for transportation, especially in densely populated urban areas. Railroad system has big potential to be the solution of the transportation problems. Communication-Based Train Control (CBTC) is one of the development of railway system which use moving-block signaling system. In is expected that moving block signalling will realise greater line capacity through shortened headways between trains. In this research train miniature is used for the experiment along with Indoor Positioning System (IPS), Radio Frequency Identification (RFID), and encoder as sensors. Position and speed data from those sensors are sent to the computer to be proccessed using the Unscented Kalman Filter (UKF) algorithm. The estimation of train miniature position is used for synchronisation control algorithm. From this research, it is known that UKF algorithm is able to produce a good estimation of train miniature position and thus synchronisation control algorithm can be applied.